2009
DOI: 10.1590/s0031-10492009003600001
|View full text |Cite
|
Sign up to set email alerts
|

The genus Oxyrhopus (Serpentes: Dipsadidae: Xenodontinae) in Guyana: morphology, distributions and comments on taxonomy

Abstract: Considerable confusion exists regarding taxonomy and distributions of Oxyrhopus in northern South America. Specimens and records of Oxyrhopus from Guyana were examined. Oxyrhopus melanogenys, O. occipitalis and O. petola occur in Guyana. Data on morphology and colouration of these species are presented. Species distributions and characters to distinguish among the species are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…Although Tozetti et al (2017) considered Oxyrhopus formosus to be endemic to the Atlantic Forest, its distribution is unclear with records scattered through the Brazilian, Ecuadorian, and Peruvian Amazon (Catenazzi et al 2013;Wallach et al 2014;Costa and Bérnils 2018). This taxon is considered a species complex with populations in Guyana, Colombia, and some places in Ecuador having been reidentified as O. occipitalis (Lynch 2009;MacCulloch et al 2009). In the Atlantic Forest, O. formosus is considered a rare species categorized as EN in the state of Bahia (Argôlo 2004;SEMA 2017), and reported from four localities within this biome: Almadina and Coaraci (Argôlo et al 2012;Dias et al 2014b) and Mucuri, the type locality (sensu Vanzolini and Myers 2015), all in the state of Bahia; and Duas Barras in Espírito Santo state (Tonini et al 2010).…”
Section: Conservation Statusmentioning
confidence: 99%
“…Although Tozetti et al (2017) considered Oxyrhopus formosus to be endemic to the Atlantic Forest, its distribution is unclear with records scattered through the Brazilian, Ecuadorian, and Peruvian Amazon (Catenazzi et al 2013;Wallach et al 2014;Costa and Bérnils 2018). This taxon is considered a species complex with populations in Guyana, Colombia, and some places in Ecuador having been reidentified as O. occipitalis (Lynch 2009;MacCulloch et al 2009). In the Atlantic Forest, O. formosus is considered a rare species categorized as EN in the state of Bahia (Argôlo 2004;SEMA 2017), and reported from four localities within this biome: Almadina and Coaraci (Argôlo et al 2012;Dias et al 2014b) and Mucuri, the type locality (sensu Vanzolini and Myers 2015), all in the state of Bahia; and Duas Barras in Espírito Santo state (Tonini et al 2010).…”
Section: Conservation Statusmentioning
confidence: 99%
“…Outgroup taxa were coded by analysis of prepared material (Appendix S2) and by data available in the literature (e.g., Albuquerque & D'Agostini, 2000;Albuquerque & Lema, 2008;Bernardo et al, 2012;Dixon, 1980;Ferrarezzi, 1993;Gans, 1964;McCulloch et al, 2009;Passos et al, 2010;Schwartz & Henderson, 1991;Zaher, 1996Zaher, , 1997Zaher, , 1999. All characters and character states descriptions are available as (Appendix S4).…”
Section: Morphological Datamentioning
confidence: 99%
“…Oxyrhopus petolarius has been recorded twice in Paraguay, once in Puerto Bertoni (Academy of Natural Sciences of Philadelphia, Philadelphia, USA, voucher ANSP 32581), and also in the Itaipú complex of protected areas (Museo Ambiental de Itaipú,Hernandarias,Paraguay,vouchers MAI 61,62,81,and 94,without precise Oxyrhopus petolarius (Linnaeus, 1758) is a medium size snake belonging to the tribe Pseudoboini (Zaher et al 2009;Grazziotin et al 2012) with an evident ontogenetic color change (Giraudo 2001). It is characterized by a black dorsum with anterior white and posterior red bands but with black snout, adults with iridescent black dorsum with reddish diffuse bands (not forming triads) and yellowish venter, 19/19/17 dorsal scales rows, 160-211 ventrals, and 81-101 subcaudal pairs (Giraudo 2001;MacCulloch et al 2009;Lopez and Prado 2012). Often recorded under the name Oxyrhopus petola, after taxonomic revision Savage (2011) concluded that the correct name for the species is Oxyrhopus petolarius.…”
mentioning
confidence: 99%
“…Often recorded under the name Oxyrhopus petola, after taxonomic revision Savage (2011) concluded that the correct name for the species is Oxyrhopus petolarius. The species has a broad distribution and is found southern Mexico, through Central America, and into South America (Bailey 1970;Lynch 2009;MacCulloch et al 2009). At the east of the Andes, it is known to occur south to the northernmost extreme of Provincia Misiones in Argentina (Bailey 1970;Giraudo 2001;Giraudo and Scrocchi 2002;Lopez and Prado 2012).…”
mentioning
confidence: 99%